2007
DOI: 10.1038/labinvest.3700677
|View full text |Cite
|
Sign up to set email alerts
|

Lack of hepatocellular CD10 along bile canaliculi is physiologic in early childhood and persistent in Alagille syndrome

Abstract: Many tissues, including hepatobiliary cells, express neutral endopeptidase (CD10), encoded by MME. Serum neutral endopeptidase activity (NEA) has been recommended as a marker of cholestasis in adults but not in children with Alagille syndrome (AGS). We investigated ontogenic and disease-related differences in the expression of CD10. CD10 was found on canalicular surfaces of hepatocytes throughout the lobule in 16 adults and in 31 children aged Z24 months, with and without cholestasis, but not in 39 children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…6,22 In the gastrointestinal tract, CD10 expression is limited to microvilli of the small intestinal and biliary epithelium, where it regulates the concentration of bradykinin, cholecystokinin, and other bioactive substances in the postsecretory modification of bile. 4,5,24 The immunostaining pattern of CD10 in the intestinal villi, gallbladder, and bile ducts is consistently strong with continuous apical expression on the brush border, 14,21,30 whereas in hepatocytes CD10 expression is discontinuous, with patchy apical labeling with a canalicular distribution. 4,6,13,21 A few reports also showed that CD10 expression is mostly preserved in benign lesions such as hepatic bile duct adenoma, 36 pyloric gland adenoma of the gallbladder, 24 and benign intrahepatic bile ducts.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…6,22 In the gastrointestinal tract, CD10 expression is limited to microvilli of the small intestinal and biliary epithelium, where it regulates the concentration of bradykinin, cholecystokinin, and other bioactive substances in the postsecretory modification of bile. 4,5,24 The immunostaining pattern of CD10 in the intestinal villi, gallbladder, and bile ducts is consistently strong with continuous apical expression on the brush border, 14,21,30 whereas in hepatocytes CD10 expression is discontinuous, with patchy apical labeling with a canalicular distribution. 4,6,13,21 A few reports also showed that CD10 expression is mostly preserved in benign lesions such as hepatic bile duct adenoma, 36 pyloric gland adenoma of the gallbladder, 24 and benign intrahepatic bile ducts.…”
mentioning
confidence: 96%
“…4,5,24 The immunostaining pattern of CD10 in the intestinal villi, gallbladder, and bile ducts is consistently strong with continuous apical expression on the brush border, 14,21,30 whereas in hepatocytes CD10 expression is discontinuous, with patchy apical labeling with a canalicular distribution. 4,6,13,21 A few reports also showed that CD10 expression is mostly preserved in benign lesions such as hepatic bile duct adenoma, 36 pyloric gland adenoma of the gallbladder, 24 and benign intrahepatic bile ducts. 4,32 In contrast, intrahepatic cholangiocarcinomas were negative to CD10.…”
mentioning
confidence: 96%
“…Membrane fractions were prepared essentially as previously described. 26,27 The blots shown are representative of two separate transfections for each mutant. For each set of transfections and subsequent membrane preparations, there was always a control experiment with wild-type BSEP, and so the mutants were always standardized to the 100% expression level of wild-type processed at the same time.…”
mentioning
confidence: 99%
“…One gel was stained with Coomassie blue to confirm uniformity of protein loading among samples. The contents of the other gel were western blotted as previously described, 26 except using a 1:300 dilution of an anti-hemagglutinin (Y-11) polyclonal primary antibody (Santa Cruz Biotechnology, Santa Cruz, CA) and a 1:1,000 dilution of horseradish peroxidase- conjugated goat anti-rabbit secondary antibody (DAKO, Ely, UK).…”
mentioning
confidence: 99%
See 1 more Smart Citation